2009
DOI: 10.1289/ehp.11533
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Traffic-Related Air Pollution and Mortality in Toronto, Ontario, Canada

Abstract: BackgroundChronic exposure to traffic-related air pollution (TRAP) may contribute to premature mortality, but few studies to date have addressed this topic.ObjectivesIn this study we assessed the association between TRAP and mortality in Toronto, Ontario, Canada.MethodsWe collected nitrogen dioxide samples over two seasons using duplicate two-sided Ogawa passive diffusion samplers at 143 locations across Toronto. We calibrated land use regressions to predict NO2 exposure on a fine scale within Toronto. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(151 citation statements)
references
References 31 publications
8
137
1
5
Order By: Relevance
“…The study compared mortality and pollution between populated regions and was not designed to investigate smaller scale variations in pollution (Krewski et al, 2009). By contrast, a cohort study in Toronto, using land use regression to predict NO 2 at the residential address and an interpolation method to predict PM 2.5 , did find a large effect on natural and cardiovascular mortality for NO 2 , but not for PM 2.5 (Jerrett et al, 2009b). Therefore, the authors modelled NO 2 together with traffic proximity (and not with PM 2.5 ), and the effects for NO 2 were slightly weakened, but still significant (from 1.40 (95% CI: 1.05-1.86) to 1.39 (95% CI: 1.05-1.85) per interquartile range of 7.6 µg NO 2 /m 3 ).…”
Section: Long Term Effects On Asthmamentioning
confidence: 98%
“…The study compared mortality and pollution between populated regions and was not designed to investigate smaller scale variations in pollution (Krewski et al, 2009). By contrast, a cohort study in Toronto, using land use regression to predict NO 2 at the residential address and an interpolation method to predict PM 2.5 , did find a large effect on natural and cardiovascular mortality for NO 2 , but not for PM 2.5 (Jerrett et al, 2009b). Therefore, the authors modelled NO 2 together with traffic proximity (and not with PM 2.5 ), and the effects for NO 2 were slightly weakened, but still significant (from 1.40 (95% CI: 1.05-1.86) to 1.39 (95% CI: 1.05-1.85) per interquartile range of 7.6 µg NO 2 /m 3 ).…”
Section: Long Term Effects On Asthmamentioning
confidence: 98%
“…Laboratory studies have indicated that inhalation of fine particles and O 3 even for a short time causes acute conduit artery vasoconstriction (Brook, 2002). Studies in Toronto have shown that exposure to traffic-related air pollution is associated with respiratory conditions (Buckeridge et al, 2002), increased risk of circulatory mortality (Jerrett et al, 2009), cardiovascular mortality (Chen et al, 2013), ischemic heart disease (Beckerman et al, 2012), and childhood atopic asthma (Shankardass et al, 2015). Research results in other locations have also shown associated negative health effects, such as asthma (Lin et al, 2002;McConnell et al, 2006), cancer and leukemia (Pearson et al, 2000) in children, and development of obesity in children (Jerrett et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…По результатам крупного популяционного исследова-ния, проведенного американскими исследователями, вы-явлено, что воздействие загрязнения воздуха существенно повышает смертность от нарушений кровообращения [11]. Z. Qian и соавт.…”
Section: Discussionunclassified